2015
DOI: 10.1007/s40725-015-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Community Wildfire Preparedness: a Global State-of-the-Knowledge Summary of Social Science Research

Abstract: This article builds on findings from a synthesis of fire social science research that was published from 2000 to 2010 to understand what has been learned more recently about public response to wildfires. Two notable changes were immediately noted in the fairly substantial number of articles published between 2011 and 2014. First, while over 90 % of the articles found in the initial synthesis were US-based studies, roughly half of the articles published since 2010 have been conducted outside the USA, the majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(90 citation statements)
references
References 89 publications
2
67
0
2
Order By: Relevance
“…Importantly, participants' attention to variation in manifestations of adaptation across community contexts was articulated by most of the study respondents and echoed research that demonstrates the importance and diversity of community characteristics (McCaffrey 2015, Paveglio et al 2015. Further, most participants discussed the fact that scaling up beyond the household level entails processes that involve more stakeholders and that the interdependency among sectors increases-both facilitating and necessitating engagement with more stakeholders.…”
Section: Translation From the Concept Of Adaptation To Communities Pmentioning
confidence: 91%
See 1 more Smart Citation
“…Importantly, participants' attention to variation in manifestations of adaptation across community contexts was articulated by most of the study respondents and echoed research that demonstrates the importance and diversity of community characteristics (McCaffrey 2015, Paveglio et al 2015. Further, most participants discussed the fact that scaling up beyond the household level entails processes that involve more stakeholders and that the interdependency among sectors increases-both facilitating and necessitating engagement with more stakeholders.…”
Section: Translation From the Concept Of Adaptation To Communities Pmentioning
confidence: 91%
“…Community case studies address this limitation, in part, by highlighting the importance of examining this intersection by placing hazard coping behaviors within local contexts to provide insights into how contextual characteristics and local histories shape response to wildfire risk (McCaffrey et al 2013, McCaffrey 2015. Such efforts build understandings of the function of local social systems but often face limitations in comparability across context due to the scale of inquiry.…”
Section: Fire Adaptationmentioning
confidence: 99%
“…Social science research on personal mitigations has found that demographic variables are inconsistent or inconsequential as predictors of adaptive behaviors (McCaffrey 2015). Marginal exceptions include reduced performance of actions among second homeowners or parttime residents and very elderly populations, though even the latter is inconsistent.…”
Section: Vulnerability To Wildfirementioning
confidence: 99%
“…Her notable works include further understanding the role of social science research in wildfire management [241] and contributions to a synthesis focusing on how to adapt and coexist with wildfires [196]. Her recent works have included a synthesis of lessons learned in public responses to wildfires from 2010-2015 [242] and evaluating what types of information people trust and find useful during wildfire disasters [157].…”
Section: Approachmentioning
confidence: 99%